2020
DOI: 10.1002/smll.202004342
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Free Multi‐Heteroatom‐Doped Carbon Bifunctional Electrocatalysts Derived from a Covalent Triazine Polymer

Abstract: The construction of multi‐heteroatom‐doped metal‐free carbon with a reversibly oxygen‐involving electrocatalytic performance is highly desirable for rechargeable metal‐air batteries. However, the conventional approach for doping heteroatoms into the carbon matrix remains a huge challenge owing to multistep postdoping procedures. Here, a self‐templated carbonization strategy to prepare a nitrogen, phosphorus, and fluorine tri‐doped carbon nanosphere (NPF‐CNS) is developed, during which a heteroatom‐enriched cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(94 citation statements)
references
References 61 publications
1
93
0
Order By: Relevance
“…More importantly, they can also show excellent catalytic property for boosting ORR. 113,114 Their OER catalytic activity, 52 however, is evidently insufficient, largely limiting their practical Li-O 2 battery performance. 116,117 Therefore, it is necessary to employ the bifunctional cathode catalysts with excellent performance towards both ORR and OER by constructing the heterogeneous structures containing carbon materials and active OER catalytic materials.…”
Section: Carbon Supported Heterostructuresmentioning
confidence: 99%
“…More importantly, they can also show excellent catalytic property for boosting ORR. 113,114 Their OER catalytic activity, 52 however, is evidently insufficient, largely limiting their practical Li-O 2 battery performance. 116,117 Therefore, it is necessary to employ the bifunctional cathode catalysts with excellent performance towards both ORR and OER by constructing the heterogeneous structures containing carbon materials and active OER catalytic materials.…”
Section: Carbon Supported Heterostructuresmentioning
confidence: 99%
“…are usually introduced into the carbon matrix to tune the partial electronic structure and change the charge density distribution of carbon, leading to the improvement of catalytic activity. [ 163–166 ] Generally, nitrogen doping was widely investigated, and DFT calculations suggested that the carbon atoms situated at the armchair edge and adjacent to the graphitic N dopants acted as more active sites for the ORR and OER. [ 167–170 ] Marcilla et al reported a kind of CNT fiber fabricated by direct chemical vapor deposition (CVD) spinning and then treated by a facile hydrothermal reaction with urea.…”
Section: Bifunctional Oxygen Electrocatalysts For Flexible Zabsmentioning
confidence: 99%
“…The use of polymers as starting materials for synthesizing carbon based electrocatalysts have gained particular interest in the research field of ORR [41]. Doping has been used as a method to incorporate heteroatoms such as N, P, and fluorine (F) into the active sites of the carbon matrix to improve its performance [42,43]. This process requires the mixing of carbon precursors with different heteroatom sources through multiple steps [42][43][44].…”
Section: Chemically Synthesized Starting Materialsmentioning
confidence: 99%
“…Doping has been used as a method to incorporate heteroatoms such as N, P, and fluorine (F) into the active sites of the carbon matrix to improve its performance [42,43]. This process requires the mixing of carbon precursors with different heteroatom sources through multiple steps [42][43][44]. However, some research studies have been performed using a single precursor to prepare heteroatom-doped carbon as electrocatalysts for ORRs.…”
Section: Chemically Synthesized Starting Materialsmentioning
confidence: 99%